The nature of the hydrogen bond outline of a comprehensive hydrogen bond theory - Gilli, Gastone; Gilli, Paola (Oxford : Oxford University Press, 2009)
This text defines the rules for predicting H-bond energies and geometries from the properties of the interacting molecules. This new knowledge is used to investigate the molecular mechanisms in systems relevant to chemistry, biochemistry, pharmacology, crystallography, and material sciences.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Hydrogen bonding